Piety of human existence according to Antonii Surozkyi - Grytsyshyn, Volodymyr (Skhid, 2015)
The paper presents a system theological and philosophical analysis of Antonii Surozkyi's teaching regarding communication with God as the basis of human existence. The prominent and influential orthodox theologian of the 20th century Metropolitan Antonii Surozkyi proves that openness to the transcendental is characteristic of an individual. This relationship of a person with God is multidimensional and includes (1) faith as spiritual knowledge of 'the unknown', (2) religious experience as an event of meeting God, (3) cognition of the self and church community in the light of knowledge of Christ as the ideal example, (4) understanding of the self and general world history in the context of sacred history. Piety of human existence as expression of openness to God governs its moral development and mystic life as well as makes possible Christian knowledge, values and development of church culture as personal lifeworld.